2010
DOI: 10.1021/la100325c
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence-Enhanced Organogels and Mesomorphic Superstructure Based on Hydrazine Derivatives

Abstract: New low-molecular-mass organic gelators (LMOGs) bearing hydrazine linkage and end-capped by phenyl, namely 1,4-bis[(3,4-bisalkoxyphenyl)hydrozide]phenylene (BPH-n, n = 4, 6, 8, 10), were designed and synthesized. These organogelators have shown great ability to gel a variety of organic solvents to form stable organogels with the critical gelation concentration as low as 8.7 x 10(-4) mol L(-1) (0.06 wt %). The formed gel has a high gel-sol transition temperature (T(gel)) at low gelation concentration. Aggregati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 55 publications
1
46
0
Order By: Relevance
“…[1] The phenomenon defined as aggregation induced emission (AIE) has been drawing much attention [2] because of its prominent advantage in devices application for the materials working in solid state, thin film or high concentrations olution.S everal possible mechanism of AIE have been put forward through experimental analysisa nd theoretical calculation, including the restriction of intramolecular rotations, [3] J-type aggregate formation, [4] intramolecular planarization, [5] intermolecular interaction, [5b, 6] intramolecular charget ransfer, [7] the restricted access to ac onical intersection, [8] etc. [1] The phenomenon defined as aggregation induced emission (AIE) has been drawing much attention [2] because of its prominent advantage in devices application for the materials working in solid state, thin film or high concentrations olution.S everal possible mechanism of AIE have been put forward through experimental analysisa nd theoretical calculation, including the restriction of intramolecular rotations, [3] J-type aggregate formation, [4] intramolecular planarization, [5] intermolecular interaction, [5b, 6] intramolecular charget ransfer, [7] the restricted access to ac onical intersection, [8] etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] The phenomenon defined as aggregation induced emission (AIE) has been drawing much attention [2] because of its prominent advantage in devices application for the materials working in solid state, thin film or high concentrations olution.S everal possible mechanism of AIE have been put forward through experimental analysisa nd theoretical calculation, including the restriction of intramolecular rotations, [3] J-type aggregate formation, [4] intramolecular planarization, [5] intermolecular interaction, [5b, 6] intramolecular charget ransfer, [7] the restricted access to ac onical intersection, [8] etc. [1] The phenomenon defined as aggregation induced emission (AIE) has been drawing much attention [2] because of its prominent advantage in devices application for the materials working in solid state, thin film or high concentrations olution.S everal possible mechanism of AIE have been put forward through experimental analysisa nd theoretical calculation, including the restriction of intramolecular rotations, [3] J-type aggregate formation, [4] intramolecular planarization, [5] intermolecular interaction, [5b, 6] intramolecular charget ransfer, [7] the restricted access to ac onical intersection, [8] etc.…”
Section: Introductionmentioning
confidence: 99%
“…An infrequent phenomenon was observed by Ta ng's group in 2001, in which as ilole derivative is barely emissive in the dilute solution but intensively emissive in the solid phase. [1] The phenomenon defined as aggregation induced emission (AIE) has been drawing much attention [2] because of its prominent advantage in devices application for the materials working in solid state, thin film or high concentrations olution.S everal possible mechanism of AIE have been put forward through experimental analysisa nd theoretical calculation, including the restriction of intramolecular rotations, [3] J-type aggregate formation, [4] intramolecular planarization, [5] intermolecular interaction, [5b, 6] intramolecular charget ransfer, [7] the restricted access to ac onical intersection, [8] etc. Crystallization-induced emission enhancement( CIEE) and switchable lumines-cence of polymorphs were discovered on the basis of AIE subsequently,w hich showed huge potentiali nt he fields of sensore lement, data storagea nd encryption technology.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the absorption peak of the carbonyl (acetyl) group [C = O(CH 3 )] in Ca-ASP also shifted to lower wave number (1753 to 1745 cm −1 ), and the absorption peak of hydroxyl (νOH) shifted to 3238 cm −1 , indicating that a hydrogen bond was formed between the acetyl and hydroxyl groups [21]. Additional FTIR spectra were measured at 100°C and 200°C (data not shown), which indicated the strength and position of peak representing the acetyl group [C = O(CH 3 )] and hydroxyl (νOH) groups were not changed, and therefore the hydrogen bond between the acetyl group and the hydroxyl group was an intramolecular bond [22]. There were two new absorption peaks, one at 1033 cm −1 and the other at 567 cm −1 , which were due to absorption by phosphate group.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22][23] For example, we reported that tetracatenar hydrazide derivatives showed a stable columnar phase and demonstrated that intermolecular hydrogen bonding played an important role in stabilising the columnar phase. [24] In our recent article, [24][25][26] twin-tapered di-hydrazine derivatives FH-Tn (n = 6, 7, 8, 10) were reported to exhibit a hexagonal columnar phase, and the intermolecular hydrogen bonding motif between the dihydrazine groups was confirmed. We also reported other di-hydrazine derivatives such as FH-n (n = 4,6,8,10) and BPH-n (n = 6, 8, 10) exhibiting a hexagonal columnar phase or a rectangular columnar phase.…”
Section: Introductionmentioning
confidence: 94%